Sneezing during Micturition: A Possible Trigger of Acute Bacterial Prostatitis - William Derval Aiken (Case Reports in Urology)
A perfectly well 39-year-old man sneezed during micturition and developed classic features of acute bacterial prostatitis corroborated by laboratory evidence of prostatic inflammation/infection. The prostate-specific antigen level at presentation was 9.6 ng/mL and declined to 1.23 ng/mL one month later on levofloxacin. This is the first report in the medical literature of sneezing while voiding being a possible trigger of acute bacterial prostatitis. A biologically plausible mechanism is provided.